The impact of the development level of rural e-commerce on the depressive symptoms among rural older adult individuals - Xie, Xiaofeng; Wei, Siying; Zhu, Ling; Gan, Xiaoting; He, Yong; Wang, Rui (Frontiers in Public Health, 2024)
BackgroundIn the context of China, where the demographic trend of population aging intertwines with the rapid advancement of information digitalization, rural older adult individuals, who are part of a vulnerable population, are witnessing a deteriorating depression status. The proliferation of rural e-commerce, which fuels the digital economic revolution in rural areas, is concurrently affecting the depressive symptoms among rural older adult individuals.MethodsThis study uses longitudinal data from the China Health and Retirement Longitudinal Study (CHARLS) and applies a multi-period Difference-in-Differences (DID) model to explore how rural e-commerce affects the depressive symptoms among rural older adult individuals.ResultsThe findings indicate that the development of rural e-commerce can indeed improve the depressive symptoms among rural older adult individuals, with a particularly pronounced effect on those residing in the eastern and central regions of China, as well as those who do not live with their children. The mechanism analysis indicates that e-commerce improves depressive symptoms among rural older adult individuals by enhancing social interaction frequency and increasing financial support by children.ConclusionBased on these insights, we recommend a targeted approach to implementing e-commerce policies in rural areas, focusing on innovative methods to improve the depressive symptoms among rural older adult individuals.